The role of sustainability strategies for climate adaptation in enhancing institutional performance for colleges and universities is a case analysis of higher education institution development - Almusawy, Azhar Mohammed Ridh (Edelweiss Applied Science and Technology, 2025)
This research aims to study the effects that sustainability strategies (SUST) have on the institutional performance of higher education institutions (INPE) in an era characterized by a rapidly changing climate. It examines sustainability strategy's environmental, economic, social, and technological dimensions and how they affect university performance stability. Now that I've clearly stated my methodological approach, let us get into it in more detail. Two hundred sixty questionnaires were distributed to faculty members at the University of Kufa, of which two hundred forty-five were returned and deemed valid for analysis. The author used advanced statistical methods to gauge sustainability strategies' impact on institutional performance. In addition, a literature review examined best global practices in sustainability policy at colleges and universities worldwide. Turning to research findings, the use of sustainability strategies contributed more than 62% towards improving institutional performance through resource efficiency, an absolute reduction in operating costs, and a structure that links various sections of the university together socially. Environmental sustainability equally accounts for 59.3% of lowering damage done to the university campus by natural disasters. Economic sustainability supports financial stability for this city by 57.8%. Furthermore, making full use of the digital environment helps teaching efficiency to sit at 60.5% due to the integration of modern technology in educational and administrative work. Whereas universities could gain many benefits from sustainability strategies, research also discovered that this still faces many challenges in execution and hasn't fully aroused the consciousness of universities as a whole—such as institutional finance, heavy public opposition to innovation, or low understanding levels of WhatsApp. Be it resolved that higher education institutions leave out something necessary, and institutional sustainability is important under present climate change conditions. By integrating a long-term and short-term model of development for institutions, everything becomes possible: colleges and universities will emerge equipped with new life from higher education and begin towards fitness for their second career.